Konsekuensi Hukum Bagi Notaris Yang Tidak Mengumumkan Minuta Akta Menurut Undang-Undang Nomor 2 Tahun 2014 - Ismail Ali; Sulaeman; Martono; Sri Maharani (Legal Journal of Law, 2025)
This study aims to analyze the role of Notaries in the preparation of deed minutes in accordance with Law Number 2 of 2014 and the legal consequences that arise if the notary does not read the deed minutes to the interested parties. Data were collected through document studies and literature relevant to the research topic. The results of the study indicate that notaries have an important role in the entire process of preparing a deed, from the formulation to the reading of the deed minutes. In accordance with the provisions of the law, Notaries are required to read the deed minutes in front of the parties to ensure that they understand the contents of the document in full and that no party is harmed. If the Notary is negligent in carrying out this obligation, it is a serious violation that can result in legal sanctions for the Notary, including the obligation to provide compensation to the injured party. In addition, a deed that is not read by a notary is at risk of losing its status as an authentic deed, which results in a decrease in the validity of the document. In conclusion, the reading of the deed minutes by a notary is a crucial aspect in maintaining the authenticity and validity of the legal documents he prepares